2021
DOI: 10.1186/s13063-021-05616-8
|View full text |Cite
|
Sign up to set email alerts
|

A supervised exercise intervention during cancer treatment for adolescents and young adults—FiGHTING F!T: study protocol of a randomised controlled trial

Abstract: Background High-quality evidence supports the integration of exercise to mitigate treatment-related side effects in a wide range of paediatric and adult cancer cohorts. However, the implementation of exercise in adolescent and young adult (AYA) cancer patients is yet to be explored in depth. FiGHTINGF!T is a randomised controlled cross over trial designed to determine if a supervised, structured, and progressive exercise programme can reduce the decline in physical fitness (V02peak) associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…None of these studies had published data available; however, three had published protocols, according to which the results would be relevant for this study. [46][47][48]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these studies had published data available; however, three had published protocols, according to which the results would be relevant for this study. [46][47][48]…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, eight ongoing trials that may fit the inclusion criteria were identified (Supporting File S3). None of these studies had published data available; however, three had published protocols, according to which the results would be relevant for this study 46–48 …”
Section: Resultsmentioning
confidence: 99%
“…Participants were stratified to reduce bias, according to the intensity of their treatment regimen; low/moderate or high intensity treatment. Stratification was overseen by a treating clinician and based on the likelihood of myelosuppression anticipated from the treatment regimen (Supplementary material 1 ) [ 16 ]. Randomisation was undertaken via a random assignment computer generator (sealed envelope) into one of the two treatment arms: exercise group (EG) or control group (CG).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were strati ed to reduce bias, according to the intensity of their treatment regimen; low/moderate or high intensity treatment. Strati cation was overseen by a treating clinician and based on the likelihood of myelosuppression anticipated from the treatment regimen (Supplementary material 1) [17]. Randomisation was undertaken via a random assignment computer generator (sealed envelope) into one of the two treatment arms: Exercise Group (EG) or Control Group (CG).…”
Section: Experimental Designmentioning
confidence: 99%